A new method for quick and easy hemolymph collection from apidae adults - Grzegorz Borsuk (2018)
© 2017 Borsuk et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Bio-analysis of insects is increasingly dependent on highly sensitive methods that require high quality biological material, such as hemolymph. However, it is difficult to collect fresh and uncontaminated hemolymph from adult bees since they are very active and have the potential to sting, and because hemolymph is rapidly melanized. Here we aimed to develop and test a quick and easy method for sterile and contamination-free hemolymph sampling from adult Apidae. Our novel antennae method for hemolymph sampling (AMHS), entailed the detachment of an antenna, followed by application of delicate pressure to the bee's abdomen. This resulted in the appearance of a drop of hemolymph at the base of the detached antenna, which was then aspirated using an automatic pipetter. Larger insect size corresponded to easier and faster hemolymph sampling, and to a greater sample volume. We obtained 80-100 μL of sterile non-melanized hemolymph in 1 minute from one Bombus terrestris worker, in 6 minutes from 10 Apis mellifera workers, and in 15 minutes from 18 Apis cerana workers (+/-0.5 minutes). Compared to the most popular method of hemolymph collection, in which hemolymph is sampled by puncturing the dorsal sinus of the thorax with a capillary (TCHS), significantly fewer bees were required to collect 80-100 μL hemolymph using our novel AMHS method. Moreover, the time required for hemolymph collection was significantly shorter using the AMHS compared to the TCHS, which protects the acquired hemolymph against melanization, thus providing the highest quality material for biological analysis.